Release of thymol from plasticized poly(vinyl chloride) - Szulc, J.; Lewandowski, K.; Skórczewska, K.; Sadkiewicz, J. (Polimery, 2021)
The aim of the study was to assess the possibility of using thymol as a potential modifier of the bioactive properties of plasticized poly(vinyl chloride) (PVC). For this purpose, a test of releasing the active substance – thymol – from modified plasticized PVC to water was performed. The higher the thymol concentration in the polymer matrix, the more substance was released during the first days of storage. The ability of the produced materials to gradually release thymol was found, which qualifies them as materials that can be useful for the production of active packaging.